Dose-volume analysis of target volume and critical structures in computed tomography image-based multicatheter high-dose-rate interstitial brachytherapy for head and neck cancer - Akiyama, Hironori; Major, Tibor; Polgár, Csaba; Takácsi-Nagy, Zoltán (Journal of Contemporary Brachytherapy, 2017)
Purpose : To evaluate dose-volume relationships of target volume and critical structures in computed tomography (CT) image-based brachytherapy for head and neck cancer. Material and methods : Thirty-seven patients with mobile tongue, floor of mouth, and base of tongue cancer treated with brachytherapy (post-operative alone and as a boost after external beam radiotherapy [EBRT], or definitive alone or as a boost after EBRT) were selected. Treatment plans were made using post-implant CT images. The fractionation schedule was 7-15 × 3-5 Gy for post-operative (with or without EBRT), 14-15 × 3 Gy for definitive alone, and 5-10 × 3 Gy for boost treatments. For the target volume, V 100 , D 90 , and dose non-uniformity ratio (DNR) were calculated. For the mandible, spinal cord and salivary glands doses to specified volumes were reported. Results : The median values of V 100 and D 90 were 89.9% and 99.9%, respectively; the median values of DNR was 0.46. The median D 2cm 3 of the mandible and spinal cord were 48.3% and 5.8%, respectively. The ipsilateral median D 2cm 3 of parotid and submandibular glands were 6.4% and 12.5%, whereas on the contralateral side, the corresponding values were 5.3% and 7.0%, respectively. Conclusions : Using conformal treatment planning, it was desirable to keep the dose to the mandible, spinal cord, and salivary glands at an acceptable level. The quantitative plan evaluation may help us find correlations between dosimetric parameters and clinical outcome, which may lead to improve the quality of the treatment, but it requires longer follow-up and results from other studies.